Effect of Ultrasonic Impact Treatment on Microstructure and Fatigue Life of 3D Printed Ti–6Al–4V Titanium Alloy; Physics of Metals and Metallography; Vol. 124, iss. 10 - Perevalova O. B. Olga Borisovna; Panin A. V. Alexey Viktorovich; Kazachenok M. S. Marina Sergeevna; Martynov S. A. Sergey Andreevich (2023, 2023)
Title screen